Transforming the Islamic Boarding School Financial Ecosystem through the Ikhlas Card: Integrating Transaction Digitalization, Management Accountability, and Student Financial Literacy - Satria Adindi; Sumedi Sumedi (FKIP - Universitas Riau, 2026)
Financial digitalization has become an important strategy for strengthening governance and sustainability in Islamic boarding schools (pesantren) in the digital era. However, many pesantren still rely on conventional cash-based financial systems characterized by limited transparency, weak accountability, and inefficient financial administration. This study aims to analyze the implementation of the IKHLAS Card as a sharia-based digital financial system and examine its impact on financial management efficiency, institutional accountability, and students’ financial literacy at Al-Ikhlas Islamic Boarding School, West Sumbawa Regency. This research employed a qualitative case study approach. Data were collected through observation, in-depth interviews, and documentation, then analyzed using an interactive analysis model consisting of data reduction, data display, and conclusion drawing. The findings indicate that the IKHLAS Card transformed the pesantren’s financial ecosystem into an integrated digital system that improves efficiency, transparency, and financial control while fostering disciplined, responsible, and accountable financial behavior among students and administrators. This study concludes that, within the context of Pondok Pesantren Al-Ikhlas, sharia-based financial digitalization through the IKHLAS Card contributes positively to strengthening financial governance and supporting more accountable financial management practices.